Computational Prediction Study on Green Self -Compacting Concrete (GSCC) Composite Slab with Different Thickness of Steel Sheet Slab Subjected to Flexural Load - Kiing, Solomon Sie Chew (Recent Trends in Civil Engineering and Built Environment, 2021)
Self-compacting concrete (SCC) is an improved quality of concrete that used less aggregates, but higher cement content than normal concrete. It is able to flow by itself and does not require compaction. Nowadays, many researchers start to study about the cement replacement by supplementary cementitious material such as POFA and ESP to enhance the strength of concrete and reduce pollution. Yet, the researches about SCC composite slab are still lacking. In this study, 5% POFA and 2.5% ESP will be used as partial cement replacement in GSCC composite slab with different thickness of steel sheet slab. The objectives of this research are to develop a slab model using ABAQUS software and study the influence of various steel sheet slab thicknesses on ultimate load, crack pattern and load-deflection profiles of GSCC composite slab subjected to flexural load by means of finite element method. Besides, the purpose of this thesis is to perform parametric study on GSCC composite slab in term of steel sheet slab thickness. Convergence study determined the suitable thicknesses of model and validation was carried out to check the difference between results from this study and result of theoretical work. The differences should be less than 10% from the experimental results. A series of parametric study was carried out on GSCC composite slab with dimension 150 mm depth by changing the thickness of steel sheet. Upon the completion of design, influence of various steel sheet composite slab’s thicknesses will be determined. It was found that a slight difference was achieved between experimental and simulation results with an error of 4.27 % and 8.58% for control and POFA + MSA block wall respectively. It was proven that FEA by using ABAQUS was able to predict the structural behaviour of structural elements with a high accuracy level. Thus, through partially replacing the cement in producing the foamed concrete, it is capable in producing environmentally friendly building materials, reduce cement production and indirectly reduce carbon dioxide emissions to the atmosphere.